Diversiﬁcation of the Higher Education System in the Light of Scientiﬁc Communication Problems - K. Alimova Natalia (Informaciâ i Innovacii)
The article analyzes the problems of diversiﬁcation of the higher education system in the light of the problems of scientiﬁc communications.With regard to the purpose of this study, as a key point was chosen the analysis of research activities of domestic universities and in particular-publication activity, as one of the criteria for assessing the eﬀectiveness of research activities of higher education institutions. The author concludes that the role of Universities in the training of scientiﬁc personnel in Russia is growing. If this trend continues, we can say that the domestic trend of diversiﬁcation of the education system, have full or almost full compliance with global trends, where the training of scientiﬁc personnel is conducted mainly in higher education. Based on the analysis of statistical material, it is noted that the number of publications in journals of Russia and other post-Soviet States indexed in the international citation databases Scopus and Web of Science Core Collection is small compared to other countries.